Two-Surgeon Technique for Hepatic Parenchymal Transection of the Noncirrhotic Liver Using Saline-Linked Cautery and Ultrasonic Dissection - Aloia, Thomas (2005)
Objective: The purpose of this study was to analyze our experience with saline-linked cautery in hepatic surgery. Summary Background Data: Safe and efficient hepatic parenchymal transection is predicated on the ability to simultaneously address 2 tasks: parenchymal dissection and hemostasis. To date, no single instrument has been designed that addresses both of these tasks. Saline-linked cautery is now widely used in liver surgery and is reported to decrease blood loss during liver transection, but data on its exact benefits are lacking. Methods: From a single institution, prospective liver surgery database, we identified 32 consecutive patients with noncirrhotic livers who underwent resection for primary or metastatic disease using a 2-surgeon technique with saline-linked cautery and ultrasonic dissection (SLC+UD) from December 2002 to January 2004. From the same database, we identified a contemporary and matched set of 32 patients who underwent liver resection with similar indications using ultrasonic dissection alone (UD alone). Operative and anesthetic variables were retrospectively analyzed to identify differences between the 2 groups. Results: The 2 groups were equivalent in terms of age, gender, tumor histology, tumor number, and tumor size. The UD+SLC group had a decreased duration of inflow occlusion (20 minutes versus 30 minutes, P = 0.01), blood loss (150 mL versus 250 mL, P = 0.034), and operative time (187 minutes versus 211 minutes, P = 0.027). Postoperative liver function and complication rates were similar in each group. Conclusions: The 2-surgeon technique for liver parenchymal transection using SLC and UD in noncirrhotic livers is safe and may provide advantages over other techniques.